Toward more rigorous country brand assessments: the modified country brand strength index - Lahrech, Abdelmounaim (2020)
Purpose– This study focuses on country branding indices. The main purpose of this study is to build an objective country brand strength index using secondary data. The new index, the Modified Country Brand Strength Index (MCBSI), builds on Fetscherin’s (2010) Country Brand Strength Index (CBSI) but uses more rigorous methods and design to create a complementary index to be used together with the survey-based Anholt–GfK Nation Brands Index (NBI). The MCBSI also utilized human development, which is an important dimension of country brands not captured by CBSI. Design/methodology/approach– The MCBSIaddresses three significant limitations of the CBSI by using an alternative methodology in constructing the index: specifically, it uses weights for the dimensions, longitudinal data, and relative values by dividing each factor by its cross-country maximum. Findings–Ourindexranks131countriesbasedonthestrengthoftheircountrybrand.Astrongercorrelation was found between the MCBSI and NBI than between the CBSI and NBI. Practical implications– Our contribution has strong implications for both policymakers and academic researchers as it provides a tool for assessing the strength of country brands through accurate but less costly data compared to primary data collected by consultancies for country brand strength indices. The MCBSI informs country brand managers regarding how well their country brand performs across a range of critical dimensions, including export, tourism, foreign direct investments, immigration, government environment and human development. Originality/value– This study contributes to the emerging academic literature on country brand indices. Currently, there is a lack of objective measurement instruments for assessing country brands. The MCBSI is designed for this purpose to complementthe NBIbymeasuringcountrybrandswithobjectivesecondarydata. Viewed together, the NBI and our index overcome the obvious shortcomings inherent in each method by providing objective, factual data on country brand equity while providing insight into how people socially construct and evaluate nation brands.